Bis‐(3‐allyl‐4‐hydroxyphenyl) sulfone decreases embryonic viability and alters hepatic mRNA expression at two distinct developmental stages in chicken embryos exposed via egg injection. (4th December 2017) - Crump, Doug; Chiu, Suzanne; Williams, Kim L.
Abstract: Concerns surrounding the toxicological effects and environmental prevalence of bisphenol A (BPA) have increased efforts to identify suitable safer replacement alternatives. Bis‐(3‐allyl‐4‐hydroxyphenyl) sulfone (TGSH) represents a potential BPA alternative; however, exposure and ecotoxicological data are scarce. To determine effects on embryonic viability, development, and hepatic mRNA expression at 2 distinct developmental periods (midincubation [day 11] and pipping [days 20–21]), TGSH was injected into the air cell of unincubated, fertilized chicken embryos at 4 concentrations ranging from 0 to 180 μg/g egg. Concentrations of TGSH increased in a dose‐dependent manner in whole‐embryo homogenates, and the estimated median lethal dose (LD50) based on embryonic viability at midincubation was 66 µg/g (95% confidence interval = 31–142 µg/g), which is similar to the BPA LD50 (∼ 67 μg/g) reported in a previous study. Modulation of hepatic gene targets from a chicken ToxChip polymerase chain reaction (PCR) array was observed at both developmental stages. At midincubation, 21/43 genes on the PCR array were significantly altered (by >1.5‐fold) in the 180 μg/g dose group, whereas 9 and 6/43 were altered at pipping in the 9.2 and 48 μg/g groups, respectively. Predominant toxicity pathways included xenobiotic metabolism, lipid homeostasis, bile acid synthesis, and cell cycle regulation. The estrogen‐responsive gene apolipoprotein II was significantly up‐regulated in liver tissue of midincubation embryos at 180 μg/g; however, neither apolipoprotein II nor vitellogenin II were altered at the other concentrations or developmental time points. Given the importance of identifying suitable BPA replacement alternatives, the present study provides novel, whole‐animal toxicological data for a BPA replacement alternative that has an effect on embryonic viability similar to that of the compound it could replace. Environ Toxicol Chem 2018;37:530–537. © 2017 SETAC